Role socialization family erroneous and its impact on criminal behavior - دينا داود محمد (College of Education for Women, 2019)
The correct and sincere process of socialization is working on appropriate social climate in which this process is the provision, and the climate is achieved in the presence of a positive environment free of negatives and contradictions, but when there is a socialization processes inadequate and contradictory was not based on the principles of punishment and reward nor a balance between methods soft and intensity of treatment and interaction with small and adolescent does not require intensive social care formulas do not create the conditions essential items required by the successful and effective socialization, the young and the young people who are going through in such Altanisah and educational operations will be subject to behavioral and interactive distractions that may lead them to the behavioral and interactive acts intersecting with the laws and values and ideals and standards of society, and here the young and the young people are not exposed to damage, but exposed them community also as long as the repercussions of the crime does not affect the criminals alone but affects their community and great community, as a n any defect or problem exposed passes through the stages of socialization small five Kalmrahlh oral or anal sexual or adolescence or maturity or completeness commute or divorce his mother hibernate during sexual hibernation stage or adolescence or neglect and indifference to the subject of his education and hone his talents and school collected or mixing with children of bad and deviants and perverts of his peers, all of that cause deviations and behavioral problems adversely affect the daily interactions and the degree of adaptation balanced with the social environment, and this may led to delinquency and crime or commit acts Hena and intersecting with the laws of society and behavioral and interactive contexts.